2020
DOI: 10.1109/access.2020.2995608
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Method to Detect Foreign Objects for Inspecting Power Transmission Lines

Abstract: Image online monitoring technology has been widely used in transmission lines inspection, but the intelligent and efficient foreign object detection still has a gap with the ideal. In this paper, we propose a deep learning method to detect invading foreign objects for power transmission line inspection. Specifically, we design our network based on the regression strategy with oriented bounding boxes to accurately predict spatial location and orientation angle of foreign objects, as well as their categories in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…One of the practical difficulties in identifying an insulator with damaged properties is that defects can be hidden under the mooring cables or under contamination [17]. Identifying a failed component during an inspection of the electrical power system requires great experience from the operator [18], even then the human factor may bring uncertainties to the process [19].…”
Section: Related Workmentioning
confidence: 99%
“…One of the practical difficulties in identifying an insulator with damaged properties is that defects can be hidden under the mooring cables or under contamination [17]. Identifying a failed component during an inspection of the electrical power system requires great experience from the operator [18], even then the human factor may bring uncertainties to the process [19].…”
Section: Related Workmentioning
confidence: 99%
“…Haoyu Xu et al proposed to identify the possible foreign objects on the airport runway by making use of the deep convolutional network [7]. Jinguo Zhu suggested detecting the foreign objects along the electric transmission lines by using the deep learning method based on the regression strategy [8]. Deqiang He put forward a object detection method combining SSD and MobileNet, which is favorable in the detection of foreign objects under the highspeed trains [9].…”
Section: Related Workmentioning
confidence: 99%
“…The application of object detection algorithms is becoming more and more widespread [1]. There have been many studies on applying target detection algorithms to transmission line foreign object detection [2]. These studies have also demonstrated the effectiveness of deep learning applied to foreign object detection on transmission lines.…”
Section: Introductionmentioning
confidence: 99%